2017
DOI: 10.1186/s12989-017-0193-5
|View full text |Cite|
|
Sign up to set email alerts
|

Reduction of pulmonary toxicity of metal oxide nanoparticles by phosphonate-based surface passivation

Abstract: BackgroundThe wide application of engineered nanoparticles has induced increasing exposure to humans and environment, which led to substantial concerns on their biosafety. Some metal oxides (MOx) have shown severe toxicity in cells and animals, thus safe designs of MOx with reduced hazard potential are desired. Currently, there is a lack of a simple yet effective safe design approach for the toxic MOx. In this study, we determined the key physicochemical properties of MOx that lead to cytotoxicity and explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 43 publications
2
62
0
Order By: Relevance
“…The DCF assay is based on a mechanism that nonfluorescent 2’,7’-dichlorodihydrofluorescein (H 2 DCF) could be converted to the highly fluorescent DCF by oxidation. This assay has been widely used to access the radicals or abiotic reactive oxygen species (ROS) generation on nanoparticle surface 6, 8 . Co 3 O 4 nanoparticles have been demonstrated to exhibit high surface reactivity in DCF assay and were used as a positive control 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DCF assay is based on a mechanism that nonfluorescent 2’,7’-dichlorodihydrofluorescein (H 2 DCF) could be converted to the highly fluorescent DCF by oxidation. This assay has been widely used to access the radicals or abiotic reactive oxygen species (ROS) generation on nanoparticle surface 6, 8 . Co 3 O 4 nanoparticles have been demonstrated to exhibit high surface reactivity in DCF assay and were used as a positive control 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study successfully achieved tiered view of the nano-SARs of Fe 2 O 3 particles in THP-1 cells, providing substantial new insights for tailored design of ENMs by modifying their physicochemical properties to acquire desired bio-effects. This allows us to reduce the toxicities of some hazardous ENMs 7, 8, 28 , or enhance the effects of nanomedicine 5, 6, 39 . Besides of Fe 2 O 3 , the multi-hierarchical nano-SAR assessment method could be potentially extended to other ENMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like metal NPs, the most important damage of TCL-SPION is inflammation [199]. Examples of these NPs are ZnO and CuO which have a damaging effect on the immune system in the lung tissue by increasing IL-1β; they also increase cytokines expression because they change pH in the tissue [200,201]. Other studies have reported the toxic effect of CeO2 and NiO NPs on lung tissue to be the expression of TNF-α in the lung cell-line [202].…”
Section: Metal Oxide Npsmentioning
confidence: 99%